Metacognitive Strategies Used in Speaking for Presentation Class by the Fourth Semester Students of English Language Education of PGRI Ronggolawe University Tuban - Yuyun Eri Susanti; Christina Innocenti Tumiar Panggabean (Universitas PGRI Ronggolawe Tuban, 2024)
This study is intended to describe metacognitive strategies used in speaking for presentation class by the fourth semester students of English language education of PGRI Ronggolawe University Tuban. It includes 1) kinds of metacognitive strategies used by the students in speaking for presentation class 2) the most dominant strategy used by the students in speaking for presentation class and 3) their reasons of using metacognitive strategies. This study used qualitative method. The subject of the study were ten students who have high, medium and low performance level in speaking. They were three male students and seven female students. The data from the questionnaire and the interview were analyzed descriptively. The result of this study indicated that all students from high, medium, and low level used all kinds of metacognitive strategies, including centering learning strategy, arranging and planning strategy, and evaluating learning strategy, but the high level students used metacognitive strategies more often than the other levels. Centering learning strategy became the most dominant strategy used by the students from all levels, followed by evaluating learning strategy and arranging and planning strategy. The students had similar reason of using metacognitive strategies. It was to help them in learning speaking and improving their presentation skill